Evaluation of Complementary Food Prepared from Sorghum, African Yam Bean (Sphenostylis stenocarpa) and Mango Mesocarp Flour Blends - Yusufu, P.A.; Egbunu, F.A.; Egwujeh, S.I.D.; Opega, G.L.; Adikwu, M.O. (Pakistan Journal of Nutrition, 2013)
The use of Sorghum, African yam bean (Sphenostylis Stenocarpa) and Mango mesocarp (Mangifera indica) flour blends in the formulation of complementary food was studied. Traditional Weaning Food (TWF) obtained from 100% sorghum was used as the control sample. The sorghum, African yam bean and mango mesocarp flour were blended in the ratio of 5:3:2 respectively and used to formulate complementary food (SAM). The sample of complementary foods produced were subjected to chemical, functional and sensory properties analyses. The result of the chemical composition showed a significant (p